1994
DOI: 10.18174/njas.v42i1.611
|View full text |Cite
|
Sign up to set email alerts
|

Preserving genetic variance resources in commercial and non-commercial populations

Abstract: Genetic diversity is the basis for livestock breeding. Diversity within breeds may be reduced by effective breeding methods in commercial breeds; diversity between breeds may be reduced by disappearance of non-commercial breeds. Two means of preserving diversity are discussed: the development of breeding methods that aim at genetic gain yet account for loss of diversity, and the setup of gene banks to preserve current diversity for future use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…On the other hand, the evaluation of genetic contributions from ancestors to descendants is needed, as well as the development of replacement strategies that guarantee a minimum DF. Buis et al (1994) reported the establishment in the Netherlands of a genetic bank for commercial and non-commercial cattle breeds. The genetic bank is a result of the combined action of AI organizations and the government.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the evaluation of genetic contributions from ancestors to descendants is needed, as well as the development of replacement strategies that guarantee a minimum DF. Buis et al (1994) reported the establishment in the Netherlands of a genetic bank for commercial and non-commercial cattle breeds. The genetic bank is a result of the combined action of AI organizations and the government.…”
Section: Discussionmentioning
confidence: 99%
“…21 respectively, indicating that a genetic bottleneck may occur at any period of the Bank. Genetic drift may produce arbitrary changes in genetic frequencies through generations, increasing the probability of gene fixation and decreasing genetic variability (Buis et al 1994). The ratio between the effective number of founder genomes and effective number of founders Ng/fe was 0 .…”
Section: Discussionmentioning
confidence: 99%
“…This trend causes genetic diversity in cattle to decline very rapidly (Hall and Bradley 1995;Hammond and Leitch 1995). In fact, genetic diversity is the basis of cross-breeding for livestock (Buis et al 1994) because this information can be used as a starting point to increase the quantity and quality of species through artificial selection and becomes the initial knowledge B I O D I V E R S I T A S 20 (3): 783-788, March 2019 784 needed in conservation of genetic resources (Kidd et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic diversity is regarded as the basis of crossbreeding for livestock (Buis et al 1994). Information on the genetic diversity may serve as a starting point for artificial selection in an attempt to increase the quality and quantity of breed.…”
Section: Introductionmentioning
confidence: 99%